Probing Supercritical Accretion in Ultraluminous X-ray Source M82 X-1 by means of X-ray Spectral Evolution Analysis - Hafizah Izatul; Vierdayanti Kiki (EPJ Web of Conferences, 2020)
We analyze the spectral evolution of ultraluminous X-ray source (ULX) M82 X-1 by means of spectral fitting. We use selected Swift/XRT data in 2014 and 2015. The flux of M82 X-1 increased by a factor of 2-3 from 2014 to 2015. Most of the data in 2015 show greater dominance of hard component than those of 2014. Due to moderate signal-to-noise ratio, we only fit each spectrum with power-law and disk blackbody model separately. The data in 2014 are better fitted with powerlaw model based on the value of reduced-chi squared. On the other hand, both powerlaw and diskbb models showed comparable re- duced chi-squared value for the data in 2015. We found that the range of spectral index for 2014 data is 1.65 < Γ < 2.08 and for 2015 data is 1.02 < Γ < 1.95 from the powerlaw model, resembling the range for that of black hole binary system at low mass accretion rate. We obtained higher innermost disk temper- ature from the disk blackbody model, 1.20 keV < Tin < 3.63 keV, compared to that of black hole binary system in the thermal state. The calculated innermost radius of the disk, Rin, varies between 0.99 to 4.89 RS assuming 10 M0 black hole which indicates that the spectral state is not in thermal dominant state but rather we suspect that M82 X-1 exhibits greater mass accretion rate than that of the thermal dominant state.